The interaction between nanocellulose and microorganisms for new degradable packaging: A review. (1st November 2022) - Si, Yanxue; Lin, Qianqian; Zhou, Fengshan; Qing, Jianrong; Luo, Huize; Zhang, Chunliang; Zhang, Juan; Cha, Ruitao
Abstract: Nanocellulose (NC), including cellulose nanocrystals (CNCs), cellulose nanofibrils (CNFs), and bacterial cellulose (BC), has attracted a great deal of attention as a green packaging material. NC can protect food from pathogen adhesion and can be degraded by microorganisms after being discarded. In this review, we introduce preparations of NC-based film, including layer by layer (LbL) assembly, electrospinning, coating, extrusion, casting, vacuum filtration, and immersion. We summarize the interaction between microorganisms and NC, and focused on the impact of NC on microbial adhesion to surfaces and the influence of microorganisms on degradation of NC-based film. We put forward the challenges of NC faces in packaging, such as hydrophobicity, antibacterial properties, and industrialization. We finally propose future perspectives of NC-based film as the packaging material. Graphical abstract: Unlabelled Image